2007
DOI: 10.1016/j.cbpa.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a pig homologue of the human lactoferrin receptor: Expression and localization during intestinal maturation in piglets

Abstract: The presence of a small intestinal lactoferrin receptor (SI-LfR) has been suggested in the pig, but remains to be identified. LfR has been suggested to play a key role in the internalization of lactoferrin (Lf) and to facilitate absorption of iron bound to Lf. The aim of this study was to identify the pig SILfR cDNA, determine its mRNA and protein expression during different stages of intestinal development. The coding region of the pig LfR cDNA was cloned by PCR using conserved sequences among species. LfR mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…This protein also represents a promising candidate for an alternative iron source in the absence of a functional DMT1 pathway. The identification of a specific receptor for lactoferrin (LfR) in the small intestine of newborn infants [115] and suckling piglets [116] is evidence that the Lf-LfR pathway plays a role in iron absorption during early life. However, a comparison of the iron status of suckling progeny from mothers with a disrupted Lf gene and those from wild-type mothers showed that lactoferrin is not essential for iron absorption during the early postnatal period and does not play a major role in the regulation of this process [117].…”
Section: Iron Metabolism In Early Postnatal Lifementioning
confidence: 99%
“…This protein also represents a promising candidate for an alternative iron source in the absence of a functional DMT1 pathway. The identification of a specific receptor for lactoferrin (LfR) in the small intestine of newborn infants [115] and suckling piglets [116] is evidence that the Lf-LfR pathway plays a role in iron absorption during early life. However, a comparison of the iron status of suckling progeny from mothers with a disrupted Lf gene and those from wild-type mothers showed that lactoferrin is not essential for iron absorption during the early postnatal period and does not play a major role in the regulation of this process [117].…”
Section: Iron Metabolism In Early Postnatal Lifementioning
confidence: 99%
“…During the first hours of life the gut is permeable to many immunologically relevant proteins such as IgA and growth factors necessary for gut development (Commare and Tappenden 2007). After the first few days of life the gut becomes impermeable to most proteins, however there is a 105 kDa lactoferrin receptor (also known as intelectin) that specializes in mediating uptake of lactoferrin into enterocytes and crypt cells (Kawakami and Lönnerdal 1991;Liao et al 2007Liao et al , 2012, so infants can transport lactoferrin past gut closure. Once lactoferrin is taken up by enterocytes at the brush border, is internalized into compartments in the apical cytoplasm, where it can have effects on cellular proliferation and directing immune responses (Nielsen et al 2010).…”
Section: Lactoferrinmentioning
confidence: 97%
“…Recombinant human lactoferrin was also shown to resist digestion in vitro [35]. A receptor for lactoferrin was iso-lated and characterized [36], and it was subsequently cloned in the human [37], mouse [38], and pig [39], all species with milk having high concentrations of lactoferrin. The LfR is a homo-trimer of about 110 kDa in molecular weight, and it is glycosylated [37].…”
Section: Absorption Of Iron From Lactoferrinmentioning
confidence: 99%
“…Interestingly, the expression is similarly high in duodenum, jejunum, and ileum [39], possibly allowing lactoferrin-iron uptake throughout the small intestine, whereas the uptake of ferrous iron (mediated by DMT-1) only occurs in the duodenum. This may be one reason why iron absorption is lower from infant formula (where iron is added as ferrous sulfate) than from breast milk [44].…”
Section: Absorption Of Iron From Lactoferrinmentioning
confidence: 99%